Can decreased cost-sharing reduce the vulnerability of sick families to poverty? An analysis of the multi-level social health insurance scheme in China. Issue 1 (19th September 2022) - Dong, Shiju; Fu, Wenhao; Yu, Zexuan; Li, Jiajia
Abstract: In recent years, China has been increasing social health insurance benefits to alleviate poverty due to illness. In 2015, China introduced the Critical Illness Insurance for patients with high out-of-pocket expenses as supplementary to the social health insurance, which categorized patients with different medical expenses into different cost-sharing policies. We conducted a survey on households with high-cost patients in rural Shandong in 2019 and employed the instrumental variables estimation approach to determine how different cost-sharing measures affect households' poverty vulnerability. We found that cost-sharing reduction significantly decreases the vulnerability of sick families to poverty. Moreover, we found that the positive effect is attributed to a reduction in health burden and household livelihood capital shocks. The vulnerability to poverty is still exceptionally high owing to the heavy health burden in rural China and other developing countries. The results of our study provide insights into poverty alleviation by improving social health insurance in developing economies.